2021
DOI: 10.1038/s41598-021-85521-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of pistol grip deformity in Japanese local residents

Abstract: Pistol grip deformity (PGD) may be the main factor in femoroacetabular impingement development. This study aimed to clarify the epidemiological indices and factors related to PGD in Japanese people. This population-based cohort study included 1575 local Japanese residents. PGD, center edge angle, and joint space width were measured radiographically. We investigated the relationship between PGD and spino-pelvic parameters. Factors associated with PGD were examined using multiple logistic regression analysis, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Study selection. Eighteen studies met the inclusion criteria and were included in this meta-analysis 16,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . The search across PubMed, EMBASE, Scopus, and the Cochrane Collaboration Library yielded 216 citations.…”
Section: Resultsmentioning
confidence: 99%
“…Study selection. Eighteen studies met the inclusion criteria and were included in this meta-analysis 16,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . The search across PubMed, EMBASE, Scopus, and the Cochrane Collaboration Library yielded 216 citations.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pathology of cam deformities has not yet been elucidated. Taniguchi et al [4] reported the prevalence of PGD and related factors in the same participants. However, the prevalence of PGD is low in Japanese individuals, and quantitative evaluation of PGD is di cult.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 1,480 participants (491 men and 989 women; mean age, 65.3 years) were included in this study. The inclusion and exclusion processes detailed above were based on those in a previous study [4]. Participant characteristics are listed in Table 5.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because several other musculoskeletal manifestations, including joint laxity, fragile intervertebral disc, vertebral scalloping caused by dural ectasia, and osteopenia, are all supposed to have an impact on the spinal column stability, the actual contribution of the altered property of paraspinal muscles on the development of characteristic spinal deformity in MFS is still unknown. [42,43] Thus, there is a need for further investigation on whether improvements in the paraspinal muscles can change the clinical course of these patients.…”
Section: Discussionmentioning
confidence: 99%